Investigate mechanical properties of laminate flax fabric composite plate with different laminate code lamination - Nurul Farhanah Mohd Salehuddin (School of Manufacturing Engineering, University Malaysia Perlis, 2016)
This paper studied the mechanical behavior of laminated flax fabric composite plate with different laminate code lamination. the aim of the study is to observe the influence of the different angle in the specimen either it contribute to the eigh mechanical of properties of the specimen or not. this is because the composite material should have the improvement in order to increase their strength that can be used in more field. the two testing that involve in this experiment to meansure the properties of laminate composite are tensile and flexurul testing.